Isolation and Identification of Pyrene Mineralizing Mycobacterium spp. from Contaminated and Uncontaminated Sources - Christopher W. M. Lease; Richard H. Bentham; Sharyn E. Gaskin; Albert L. Juhasz (Applied and Environmental Soil Science)
Mycobacterium isolates obtained from PAH-contaminated and uncontaminated matrices were evaluated for their ability to degrade three-, four- and five-ring PAHs. PAH enrichment studies were prepared using pyrene and inocula obtained from manufacturing gas plant (MGP) soil, uncontaminated agricultural soil, and faeces from Macropus fuliginosus (Western Grey Kangaroo). Three pyrene-degrading microorganisms isolated from the corresponding enrichment cultures had broad substrate ranges, however, isolates could be differentiated based on surfactant, phenol, hydrocarbon and PAH utilisation. 16S rRNA analysis identified all three isolates as Mycobacterium sp. The Mycobacterium spp. could rapidly degrade phenanthrene and pyrene, however, no strain had the capacity to utilise fluorene or benzo[a]pyrene. When pyrene mineralisation experiments were performed, 70–79% of added 14C was evolved as 14CO2 after 10 days. The present study demonstrates that PAH degrading microorganisms may be isolated from a diverse range of environmental matrices. The present study demonstrates that prior exposure to PAHs was not a prerequisite for PAH catabolic activity for two of these Mycobacterium isolates.